Pengaruh Model Pembelajaran Kooperatif Tipe STAD Dan Kecerdasan Interpersonal Terhadap Hasil Belajar Pendidikan Kewarganegaraan Siswa Kelas X SMA Negeri 3 Pandeglang - Toto Purwanto (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
The purposes of this research is to determine:(1) The difference between students’ learning achievement of civics education between students who learn by using cooperative learning STAD model and using expository method (lecture); (2) the difference between students’ learning achievement of civics education between students who have high interpersonal intelligence and students who have low interpersonal intelligence; (3) the interaction of applying cooperative learning STAD model and interpersonal intelligence toward civics learning achievement; (4) the difference students’ learning achievement of civics education between the students using cooperative learning STAD model who have high interpersonal intelligence and the students using expository learning method who have high interpersonal intelligence; and (5) the difference learning achievement of civics education between the students using cooperative learning STAD model who have low interpersonal intelligence and the students using expository learning method who have low interpersonal intelligence.This research uses quantitative approach with experimental method. The results show (1) students’ civics education achievement by applying cooperative STAD learning model is higher than students’ civics education achievement by expository learning method; (2) students’ civics education achievement who has high interpersonal intelligence is higher than students’ civics education achievement who has low interpersonal intelligence; (3) there is interaction between applying cooperative STAD learning model and high interpersonal intelligence towards students’ civics education achievement; (4) students’ civics education achievement who has high interpersonal intelligence by applying cooperative STAD learning model is higher than the students’ civics education achievement who has high interpersonal intelligence by applying expository learning method; and (5) students’ civics education achievement who has low interpersonal intelligence by applying cooperative STAD learning model is higher than the students’ civics education achievement who has low interpersonal intelligence by applying expository learning method.